A multicenter analysis to identify the risk factors for stroke recurrence and mortality within 1 year - Eman A. Alraddadi; Eman A. Alraddadi; Hashim F. Alotaibi; Hashim F. Alotaibi; Yasser Alatawi; Ahmed Aljabri; Ahmed A. Alghamdi; Ahmed A. Alghamdi; Fahad Alturki; Fahad Alturki; Faisal F. Alamri; Faisal F. Alamri (Frontiers in Neurology)
BackgroundStroke recurrence is a serious and prevalent complication of ischemic stroke that warrants additional investigation.MethodsA hospital-based retrospective observational study included acute-subacute ischemic stroke adult patients. The primary aim was to determine the risk factors associated with recurrent stroke within 365 days. Additionally, a combined outcome consisting of any stroke recurrence or all-cause mortality within 365 days was considered secondary outcome. Univariate and multivariable Cox proportional-hazards models were used to examine the association of risk factors with stroke recurrence and composite death/stroke recurrence.ResultsOf 1,244 patients, 112 (9%) experienced stroke recurrence. The multivariable analysis identified risk factors for stroke recurrence including history of previous stroke (HR = 3.65, 95% CI:2.28–5.99, p = 0.0001), tissue plasminogen activator (tPA) treatment (HR = 2.84, 95% CI:1.57–4.86, p = 0.0003), seizure (HR = 1.96, 95% CI:1.14–3.22, p = 0.0105), and depression (HR = 2.26, 95% CI:1.33–3.69, p = 0.0016). Only previous stroke history (HR = 2.37, 95% CI:1.74–3.26, p = 0.0001) remained significantly associated with the combined outcome of stroke recurrence/death. Additional risk factors for the composite outcome included older age of patients (HR = 1.02, 95% CI:1.01–1.03, p = 0.0009), admission to the intensive care unit (ICU) (HR = 3.70, 95% CI:2.63–5.22, p = 0.0105), pneumonia (HR = 1.47, 95% CI:1.05–2.05, p = 0.0249), and brain edema (HR = 2.36, 95% CI:1.58–3.46, p = 0.0001).ConclusionKey findings include a stroke recurrence rate of 9.96% and a combined death/stroke recurrence rate of 21.83% within 365 days. Multivariable analysis confirmed that history of stroke, receiving tPA, experiencing seizures, and depression were significantly associated with stroke recurrence. Implementing additional preventive measures for individuals in these high-risk categories is essential. Further studies are needed to validate our findings.